On finite MTL-algebras that are representable as poset products of archimedean chains - Castiglioni, José Luis (2020)
We obtain a duality between the category of locally unital finite MTL-algebras and the category of finite labeled trees. In addition we prove that certain poset products of MTL-algebras are in fact, sheaves of MTL-chains over Alexandrov spaces. Finally we give a concrete description for the studied poset products in terms of direct products and ordinal sums of finite MTL-algebras.